Analysis of the Effect of Additional Number of 24, 26 And 28 Blade of Pelton Turbine from PLA to Turbine Performance - Mahardika, Shultoni; Sugiono, Didik; Irwansyah, Rizal; Supardi; Novianto, Hernawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
Indonesia is currently unable to provide 100% electricity supply for its people due to uneven access to infrastructure development. This causes the need to build alternative energy to meet these needs. Water flow has potential energy that has been widely used in various countries to be converted into electrical energy. One way of converting is with a Pelton turbine. A Pelton turbine can work well, influenced by several parameters, namely the height of the waterfall, the angle of the blades, the flow rate, the number of nozzles, the number of blades, the weight of the turbine, etc. In this study the parameters set were the flow rate according to the pump flow rate, namely 18 liters/minute, the number of turbine blades used were 24, 26 and 28 pieces. The diameter of the turbine runner is 300 mm, and the load used in measuring the current is 50 watts. The results showed that the higher the rotational speed, the higher the turbine power, along with the increasing number of blades tested. The highest turbine power is at 28 blades and the turbine rotation is 385.42 Rpm which is 5.69 watts. While the lowest is at 24 blades and turbine rotation of 367.95 Rpm which is equal to 4.83 watts. The power difference between blades 24 and 28 is 15%. The PLA material used as the turbine blade material and acrylic as the runner material results in the moment of inertia of the turbine when rotating at blade 24 which is 0.023 kg.m² and blade 28 which is 0.025 kg.m². The mass of the turbine becomes lighter resulting in the power difference between blades 24 and 28 not being too far.